O método crítico de Sebastião Uchoa Leite - Monteiro, Éversom Pinto (2013)
This work aims to analyse the critic method of Sebastião Uchoa Leite, considering some of his essays, of the paper works: Participação da palavra poética (1966), Crítica Clandestina (1986), Jogos e enganos (1995) and Crítica de ouvido (2003). Due to his influences based on the Estruturalism, that was again discussed in the mid of the XX century in Brazil and with great influence of Luiz Costa Lima, Uchoa Leite shows thoughts of appreciation of the work with the language and aesthetics and he looks for an effective method for the written expression, critic and poetic, for the author leaves a legacy for literature. The ideal situation would be the formation of a critic-poet, whose critic and poetic dialogue with similar characteristics, in a circular thougt that, would produce more questions than answers: that s the language game: his method or as it called, by the author, ―antimethod‖.